Eficacia del concreto y la baritina como atenuadores de rayos X. Una revisión de la literatura - Huañec Huillca, Fiorella Francesca (2020)
The safety of the use of radiation in odontology must be guaranteed in order to avoid adverse effects to the health of dental staff and patients. The present study is a review of the literature on exposure to ionizing radiations and the advantages and properties which simple concrete and barite provide as shielding material in wall design and construction in areas of odontology in which X-rays are used. The general characteristics of X-rays which make them harmful to exposed workers and the general public are described. An attenuation coefficient is the fraction of an x-ray beam that is absorbed or scattered per unit thickness of the absorber. There is little information on this subject, however, it was found that both concrete and barite are able to block and reduce the intensity of radiation, with concrete acting as an absorbent to reduce the biological effects of radiation and barite acting as a shield. Based on the coefficient of attenuation these two materials provide greater resistance and their combined use allows greater protection against exposure to ionizing rays.